A generic business process model for conducting microsimulation studies - Jan Pablo Burgard; Hanna Dieckmann; Joscha Krause; Hariolf Merkle; Ralf Münnich; Kristina M. Neufang; Simon Schmaus (Statistics in Transition New Series, 2020)
Microsimulations make use of quantitative methods to analyze complex phenomena in populations. They allow modeling socioeconomic systems based on micro-level units such as individuals, households, or institutional entities. However, conducting a microsimulation study can be challenging. It often requires the choice of appropriate data sources, micro-level modeling of multivariate processes, and the sound analysis of their outcomes. These work stages have to be conducted carefully to obtain reliable results. We present a generic business process model for conducting microsimulation studies based on an international statistics process model. This simplifies the comprehensive understanding of dynamic microsimulation models. A nine-step procedure that covers all relevant work stages from data selection to output analysis is presented. Further, we address technical problems that typically occur in the process and provide sketches as well as references of solutions.
Keywords: 519; multi-source analysis; multivariate modeling; social simulation; synthetic data generation